Techno-Functional and Bioactive Properties and Chemical Composition of Guava, Mamey Sapote, and Passion Fruit Peels - Leticia X. López-Martínez; Mónica A. Villegas-Ochoa; J. Abraham Domínguez-Avila; Elhadi M. Yahia; Gustavo A. Gonzalez-Aguilar (Polish Journal of Food and Nutrition Sciences, 2023)
Due to their nutritional and sensorial characteristics, tropical fruits like guava, mamey sapote, and passion fruit are regularly incorporated into daily diets. Their by-products, especially peels, are approximately 10 to 35% of their weight and possess an important content of bioactive compounds, such as dietary fiber and phenolics. The nutritional, technological, physio-functional properties and phenolic compound compositions of guava, mamey sapote, and passion fruit peels were studied. Peels had promising techno- and physio-functional characteristics, good dietary fiber contents (45.18-61.42 g/100 g), and phenolic profiles with ferulic acid, gallic acid, p -coumaric, and catechin as the main compounds. Peel powders also showed excellent DPPH radical scavenging activity (125.3–252.4 µmol TE/100 g) and Trolox equivalent antioxidant capacity, TEAC (369.2–656.8 µmol TE/100 g). The α-amylase and lipase inhibitory activity varied from 28.15 to 51.4% and 30.89 to 57.15%, respectively. Higher values of α-glucosidase inhibition capacity were found, ranging from 51.64 to 70.32%. The chemical composition and properties reported in the present work suggest that peel powders of these guava, mamey sapote, and passion fruit could be used as constituents in different foods, such as bakery and meat goods, with beneficial health effects like control of hyperglycemia, improved intestinal function, and control of overweight; however, more studies are necessary for animal models and humans to confirm these bioactivities conclusively.